1966
DOI: 10.1063/1.1720039
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Neutron Diffraction Furnace

Abstract: An induction transformer furnace for a neutron diffractometer is described. This furnace has been used for the examination of refractory carbides by neutron diffraction at temperatures up to 2500°C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

1968
1968
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…The composition ThC1.9v obtained from the analysis is in excellent agreement with a recent determination of the phase boundary (Satow, 1967). A second sample of nominal composition THC2.25 was examined by thermal analysis (Rupert, 1965) and by high-temperature neutron diffraction (Bowman, Hull, Witteman, Arnold & Bowman, 1966). Diffraction patterns were obtained from 20= 15 to 70 ° at 1150, 1450 and 1550°C, and were corrected by subtracting a blank run on the graphite sample holder.…”
mentioning
confidence: 99%
“…The composition ThC1.9v obtained from the analysis is in excellent agreement with a recent determination of the phase boundary (Satow, 1967). A second sample of nominal composition THC2.25 was examined by thermal analysis (Rupert, 1965) and by high-temperature neutron diffraction (Bowman, Hull, Witteman, Arnold & Bowman, 1966). Diffraction patterns were obtained from 20= 15 to 70 ° at 1150, 1450 and 1550°C, and were corrected by subtracting a blank run on the graphite sample holder.…”
mentioning
confidence: 99%
“…Several high temperature techniques have been developed for determination of physical properties such as melting points [1,2], vaporization characteristics [3], or vapour pressures [4], thermodynamic data [5][6][7][8][9], electric conductivity [10][11][12][13], thermal conductivity [14][15][16] and thermal expansion [ 17-21 in temperature ranges above 2 000 K. The begining of very high temperature X-ray diffraction experiments [22] first contributed to the measurement of thermal expansion of refractory metals [23], progressing to the study in situ of high temperature phase transitions. High temperature neutron diffraction experiments have more recently been developed [24]. Although neutron scattering heating devices are significantly inspired by the numerous approaches tried for X-rays, the neutron devices are at present simpler as will be shown in the present review.…”
Section: Introductioamentioning
confidence: 99%
“…-Four kinds of heating techniques have been used in X-ray diffraction experiments : i) induction heating, with electrically conducting samples that are directly heated when placed in the centre of the work coil ; insulators can only be indirectly heated by thermal conduction and mainly by radiation. It is of interest to note that the latter method was the first to be used both for high temperature X-ray [22,23,25], and neutron diffraction experiments [24]. The Bowman et al's neutron diffraction furnace [26] is shown in figure 1.…”
Section: Introductioamentioning
confidence: 99%
“…The composition by chemical analysis was LaC2.0 with < 500 ppm oxygen and free carbon. The sample was examined by high-temperature neutron diffraction (Bowman, Hull, Witteman, Arnold & Bowman, 1966) in a graphite holder under an atmosphere of flowing helium. The diffraction data were obtained from 20= 25 to 70 ° at a wavelength of * Work done under the auspices of the U.S. Atomic Energy Commission.…”
mentioning
confidence: 99%
“…The composition by chemical analysis was LaC2.0 with < 500 ppm oxygen and free carbon. The sample was examined by high-temperature neutron diffraction (Bowman, Hull, Witteman, Arnold & Bowman, 1966) 1"3926 ,~, and were corrected by subtracting a blank run on the graphite sample holder. The corrected patterns are shown in Fig.…”
mentioning
confidence: 99%